Prevalence of carbapenem-resistant Enterobacterales (CRE) in Saudi Arabia: A systematic review and meta-analysis - Ahmad A. Alshehri; Ahmad Adebayo Irekeola (Elsevier, 2024)
Antimicrobial resistance is a significant public health issue. In addressing the threat of multidrug resistant bacterial infections, carbapenems have been used. The carbapenem-resistant Enterobacterales (CRE) are, however, rapidly expanding worldwide. Since the issue of CRE is also a problem in Saudi Arabia, the current meta-analysis was performed to comprehensively evaluate the resistance rates to the main carbapenem antibiotics and determine the actual prevalence of CRE in the country. Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines was followed. Different web databases including PubMed, Scopus, Web of Science, and ScienceDirect were searched for relevant records. Data were extracted, and summary estimates for resistance to carbapenems were calculated using DerSimonian-Laird method of meta-analysis and the random-effects model. From a total of 787 retrieved records, 69 studies were found fully eligible and were included in the final analyses. More than 50 % of all the studies were conducted after 2010, and the most frequently examined members of the Enterobacterales were Escherichia coli and Klebsiella pneumoniae. The pooled prevalence estimate for imipenem resistance was 6.6 % (95 % CI: 4.7-9.2), 9.1 % (95 % CI: 6.7-12.3) for meropenem, and 18.6 % (95 % CI: 11.9-27.9) for ertapenem. High heterogeneity (I2 > 97 %, p < 0.001) was observed for all the estimates. Compared to other regions of the country, there was higher resistance rates in the Al-Qassim and Al-Jouf provinces. Additionally, resistance to ertapenem was as high as 34.2 % in the most recent study period (2021-2024). Proteus spp was the most prevalent CRE (26.2 %). This review highlights an increasing rate of carbapenem resistance among Enterobacterales, emphasizing the need for collaborative efforts to implement strict infection control and prevention measures. Consistent surveillance is indispensable for safeguarding public health, guiding clinical decisions, and strengthening efforts to tackle the challenges of antibiotic resistance.